The Role of Time Lapse(4D) Seismic Technology as Reservoir Monitoring and Surveillance Tool: A Comprehensive Review - Sambo, C. (Elsevier B.V., 2020)
An efficient reservoir surveillance and monitoring technique should be able to monitor changes in the reservoir fluid and provide a better understanding of the spatial movement and distribution of fluids over time. Unfortunately, traditional methods of monitoring and surveillance are unable to provide the detailed pieces of information. This type of knowledge is needed to support the rational reservoir management and field development decisions provided by 4D seismic technology. With recent technological advances in seismic acquisition and processing, the case for its application has been strengthened. This article, therefore, reviewed the application of 4D seismic technology in extending the life of hydrocarbon fields and improving hydrocarbon recovery, with specific consideration to the progresses made over the last decades. It also discussed the current status of developments and challenges, including monitoring issues related to subsurface carbon dioxide (CO2) storage sites, integrating 4D seismic technology with other geophysical approaches, and the growing need to monitor 4D seismic in unconventional reservoirs. Most researches emphasized that useful conclusions can be drawn by using a combination of seismic attributes instead of using them alone. Furthermore, the critical review on the published researches suggested that the 4D seismic method can be used for dynamic reservoir monitoring in the unconventional reservoir. However, the success of 4D technology in this area is based on a multi-disciplinary approach where the 4D seismic technology is integrated with geomechanics and fluid flow. Although, the review demonstrated that 4D seismic technology was used in the history matching process. However, all these workflows depend on rock physics modeling and most of the rock-physics models currently available are associated with some uncertainties. In addition, the ability to accurately monitor a CO2 during injection remains a challenge due to uncertainties associated with pore-scale variations. Several studies have highlighted that the use of other geophysical methods such as source-controlled electromagnetic (CSEM), gravity, and surface deformation for monitoring purposes in hydrocarbon reservoirs and storage is feasible. However, there are still several gaps in the literature regarding the integration of these techniques with 4D seismic. An integrated use of geophysical methods is the future direction of reservoir monitoring and surveillance from existing fields. Â© 2020 Elsevier B.V.